Marketing directo en el incremento de ventas, distribuidora Intriago y Asociados, sector norte, ciudad de Guayaquil - Alvarado Ramírez, Alexandra Stefania (2019)
Distribuidora Intriago y Asociados proposes to increase its participation in the mass consumption market in Guayaquil through digital media, to recover the company's sales and increase the promotion in online and offline media with the application of direct marketing and the recovery of inactive customers, through direct marketing, which highlights digital marketing, ecommerce, telemarketing, e-mailing, kiosks, mailbox, etc., the direct sales methods for the increase of customers of mass consumption in the In the northern sector of Guayaquil, it can be reviewed that the research is descriptive and deductive, with a mixed approach, both qualitative and quantitative. As for the frequency of purchase from retail stores to product distributors, weekly purchases are generated…….